Determinan Kinerja Keuangan terhadap Maqashid Syariah Development Indeks pada Bank Umum Syariah - Wahab, Abdul; Ali, Rahmat (Al-Buhuts, 2024)
This study aims to determine the effect of financial performance through profitability ratios proxied by return on assets (ROA), liquidity ratios proxied by financing to deposit (FDR), solvency ratios proxied by capital adequacy ratio (CAR), and efficiency ratios proxied with operational costs on operating income (BOPO) to the level of sharia compliance through the maqashid sharia development index (MSDI) which collects the five objectives of sharia, namely hifdz al-diin (maintaining religion), hifdz al-maal (protecting assets), hifdz al-nafs (maintaining the soul), hifdz al-nasl (maintaining offspring), and hifdz al-aql (maintaining reason) based on the concept of maqashid sharia version of Jasser Auda. This type of research is quantitative research with the research method used being the documentation method. Secondary data sources with purposive sampling technique. The data have been seen from the annual reports of Islamic commercial banks in Indonesia with a time period of 2011 to 2020. The data analysis method used is panel data regression analysis with Chow test, Hausman test, and hypothesis testing (R2 test, t-test, and F test), while the panel data regression estimation model used is the fixed effect model. The data processing in this study uses the E-Views 12 program. The results obtained on the effect on the level of sharia compliance through the maqashid sharia development index (MSDI) include; return on assets (prob. 0.5209), financing to deposit (prob. 0.0036), capital adequacy ratio (prob. 0.7312), and efficiency ratio proxied by operating costs to operating income/BOPO (prob. 0,1137).